An Empirical Examination of the Relationships between Service Quality, Satisfaction and Behavioral Intentions in Higher Education Setting - Dado, Jaroslav; Petrovicova, Janka Taborecka; Cuzovic, Sreten; Rajic, Tamara (Serbian Journal of Management, 2011)
The main aim of this study is to examine the relationship between service quality and customer satisfaction and their impact on behavioral intentions in higher education setting in Serbia. Two competing models, revealed during the literature review, have been tested on a sample of Engineering Management students by means of structural equation modeling, performed via LISREL 8. Results of the study indicate that satisfaction is influenced by service quality and directly related to behavioral intentions, thus offering support for Oliver’s (1999) cognition-affect-conation sequence of causal relationships in loyalty formation. Implications of the study have been discussed and limitations and directions for future research are outlined.
Keywords: competences; Service quality; Satisfaction; relationship